Investigation of Soil Physicochemical Effects on the Corrosion of Buried Iron Pipes - Jiru, Moera Gutu; Tolcha, Mesay Alemu; A. Yeshanew, Dessalegn (Journal of Basic & Applied Sciences, 2021)
Soil corrosivity was an active problem of water pipeline damaged by corrosion that affects the performance of pipe manufacturers. In Addis ababa, groundwater pipelines were facing breakage and like due to corrosion damage of the pipes. The population of nearly four million were facing a shortage of clean and continuous water supply. Maintenace and replacing old pipes with new ones increased additional cost and delay of water supply for the city. For this investigation of corrosion, causes were conducted which soil property is the one factor. Investigation of soil corrosivity for a given specific location before installation is important to design robust pipes that can serve for long life. Soil physicochemical behaviors of the soil parameters were pH, moisture content, and electrical resistivity for any type of soil. In addition, soil bulk density, total nitrogen, soil texture, and electrical conductivity were also the main factors to be studied. The laboratory result indicated that pH of 6.98-7.04, moisture content of 23.7-37.5%, and electrical conductivity of 0.105-313 ds/m were observed. Total nitrogen was small as 0.06-0.10 for a type of soil were class and loam soils. From the analysis of eight soil samples taken from different cities. The results show that the corrosivity behavior of buried iron pipes in the capital city of Ethiopia was moderately corrosive. As confirmed from various soil samples tested from corroded pipes at different depths of 40, 80, and 120 cm. The influence of soil corrosiveness factors initiates pits formation and propagates its width and depth on the surface of pipes.